2009
DOI: 10.1042/bj20081888
|View full text |Cite
|
Sign up to set email alerts
|

Lipid phosphate phosphohydrolase type 1 (LPP1) degrades extracellular lysophosphatidic acid in vivo

Abstract: Lysophosphatidic acid (LPA) is a lipid mediator that stimulates cell proliferation and growth and is involved in physiological and pathological processes such as wound healing, platelet activation, angiogenesis and the growth of tumors. Therefore, defining the mechanisms of LPA production and degradation are of interest in understanding the regulation of these processes. Extracellular LPA synthesis is relatively well understood whereas the mechanisms of its degradation are not. One route of LPA degradation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 37 publications
2
115
1
Order By: Relevance
“…The studies with the Ppap2a tr/tr mice reported a plasma half life for LPA of approximately 12 minutes as opposed to 3 minutes in wild-type mice. 34 As complete elimination of a bolus injected agent occurs within five elimination halflives, 35 there is likely to be negligible amounts of LPA left within 15 minutes of administration in the present study. Such a time frame matches BBB-disruption window observed with LPA administration in the present study.…”
Section: Studies By Yanagida K Et Almentioning
confidence: 94%
“…The studies with the Ppap2a tr/tr mice reported a plasma half life for LPA of approximately 12 minutes as opposed to 3 minutes in wild-type mice. 34 As complete elimination of a bolus injected agent occurs within five elimination halflives, 35 there is likely to be negligible amounts of LPA left within 15 minutes of administration in the present study. Such a time frame matches BBB-disruption window observed with LPA administration in the present study.…”
Section: Studies By Yanagida K Et Almentioning
confidence: 94%
“…Although ATX can clearly generate LPA in blood plasma through hydrolysis of high concentrations of circulating LPC, and this activity is important for maintaining plasma LPA levels in the Ն100 M range in the face of rapid elimination (13,14), very little is known about the extracellular concentration of LPA in tissues. Furthermore, although a role for circulating levels of the structurally related lipid mediator sphingosine 1-phosphate in control of the permeability of lymphatic and vascular endothelium is well supported by substantial data, the function of plasma LPA remains enigmatic (33).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma LPA is generated by hydrolysis of circulating lysophosphatidylcholine (LPC) catalyzed by the secreted lysophospholipase D, autotaxin (ATX) (12). ATX activity is required to sustain plasma LPA levels in the face of rapid elimination of this lipid from the circulation (13,14). ATX potently stimulates the growth and migration of many cell types and is required for vascular development in mice.…”
mentioning
confidence: 99%
“…Intraperitoneal injection of syngeneic ovarian cancer cells into LPP1 knockout mice leads to enhanced cancer cell seeding compared to wildtype mice [120] . Presumably, higher systemic levels of LPA can explain this result as a consequence of decreased LPA turnover in LPP1 knockout mice compared to wildtype controls [111,120] . Other work on targeting LPP expression or investigations to its role in tumor biology is presented later in this review.…”
Section: Lpps As Regulators Of Extracellular Lpa Signalingmentioning
confidence: 99%
“…This enables the LPPs to degrade extracellular LPA and other signaling lipids, attenuating their effects on surface receptor activation [110] . The importance of this ecto-activity has been demonstrated in vivo where the half-life of circulating LPA increases from 3 minutes to 12 minutes in LPP1 hypomorph mice compared to normal control littermates [111] . LPPs are also localized on the internal membranes including the endoplasmic reticulum [112] and Golgi network [113] , where presumably the catalytic domains face the lumenal sides of these organelles.…”
Section: Lpps As Regulators Of Extracellular Lpa Signalingmentioning
confidence: 99%